Analisis Penilaian Persediaan Obat-obatan Berdasarkan SAK EMKM Pada Apotek Nanda Medika - Sunanto; Kiki Wulan Dari; Dian Ofasari; Tika Handayani; Rahmawati Hasibuan (Journal Research of Economic and Bussiness, 2026)
This study aims to determine how the inventory of medicines is assessed using the MPKP cost formula (first entry first out) and the Weighted Average (Average) based on SAK EMKM at the Nanda Medika Pharmacy. Nanda Medika Pharmacy is a business activity that is engaged in trading various kinds of drugs. This research is a quantitative descriptive study, while the subject of this research is Nanda Medika Pharmacy, and the objects of this research are the inventory of Mexon, Dexsa, and Graze drugs. The types of data are primary data and secondary data. Data collection techniques in this study were in the form of observation, questionnaires and interviews. The type of data in the form of primary data and secondary data. The data analysis technique used is calculating drug inventory using the MPKP and Average methods based on SAK EMKM. The results of the analysis of the assessment of 3 types of drug inventory using the MPKP and Average cost formulas based on SAK EMKM at Nanda Medika Pharmacy are based on initial balance, purchase, and sales data. Based on the discussion, it was found that the assessment of drug materials at Nanda Medika Pharmacy had not yet carried out an inventory assessment using both the first-in-first-out (MPKP) method and the weighted average (Average) method and based on the results of the calculation of the cost of goods sold using the first-in-first-out (MPKP) method was lower than using the weighted average (Average) method. This will cause the profit generated from the calculation using the first-in-first-out (MPKP) method to produce a higher profit and ending balance than the weighted average (Average) calculation. Keywords: Inventory, first in first out method (MPKP), Moving Average, SAK EMKM